Foreign Investment and Residential Property Price Growth - Chris Wokker; John Swieringa (The Australian Government, The Treasury, 2016)
This study uses fixed effects panel regression techniques to estimate the impact of foreign demand for Australian residential real estate on property prices. All model specifications find a positive relationship between foreign investment approvals and price growth at the postcode level, but the majority of price growth experienced in recent times does not appear to be attributable to increased foreign demand. This is unsurprising given that in the short run the supply of residential property is relatively fixed so any increase in demand, whether domestic or foreign, should result in higher prices. Indeed, there have been many other significant domestic drivers of property prices over the period examined. The majority of foreign investment approvals are for new as opposed to established dwellings. This provides some indication that, in the longer-term, foreign demand is increasing property supply consistent with Australia's foreign investment framework.
Keywords: F21; R31; 330; Foreign Investment; Residential Real Estate; House Prices